Pengaruh Motivasi, Komitmen dan Kepuasan Kerja terhadap Kinerja Karyawan - Surono Surono; Mochamad Vrans Romi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research analyzes the influence of motivation, commitment, and job satisfaction on employee performance at Bank Rakyat Indonesia (BRI) Jayapura Branch. This research uses quantitative methods with a survey approach. The research results show a significant influence between motivation, commitment, and job satisfaction on employee performance at the BRI Jayapura Branch. It is hoped that these findings will be useful for BRI Jayapura Branch management in formulating strategies for improving employee performance through increasing motivation, commitment, and job satisfaction. In conclusion, there is an influence of motivation, commitment, and job satisfaction on employee performance at Bank Rakyat Indonesia (BRI) Jayapura Branch. Keywords: Performance, Job Satisfaction, Commitment, Motivation